EDUKASI FINANSIAL UNTUK REMAJA: STRATEGI MENINGKATKAN LITERASI DAN INKLUSI KEUANGAN DI SEKOLAH MENENGAH PERTAMA - Muttaqiin, Ninnasi; Zujajatul 'Ilmi; Moh. Saiful Hakiki; Riyan Sisiawan Putra (Penerbit Az-Zahra Media Society, 2025)
The issue of low financial understanding among teenagers, particularly students at the junior high school level, is a significant concern in shaping a generation that is financially literate and responsible. This community service activity aimed to improve financial literacy and inclusion through age-appropriate and practical financial education. The methods included interactive socialization, educational counseling, and pocket money management simulations in the form of a workshop. The partner institution was SMP Insan Cendekia Mandiri Boarding School Sidoarjo, with 45 seventh-grade students participating. Evaluation was conducted using pre- and post-tests, along with observation of students’ active engagement during the training sessions. The results indicated a 68% increase in students' understanding of basic financial management concepts, as well as enhanced soft skills in budgeting and distinguishing between needs and wants. This activity demonstrated the effectiveness of educational approaches in preparing teenagers to face future financial challenges.